2002
DOI: 10.1046/j.1365-2036.2002.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic pancreatitis — diseases on the rise: a study of hospital admissions in England 1989/90–1999/2000

Abstract: Summary Background: The number of hospital admissions for acute and chronic pancreatitis increased in Britain from the 1960s to the 1980s. Aims: To determine time trends in acute and chronic pancreatitis for hospital admissions from 1989/90 to 1999/2000, mortality from 1979 to 1999, and various indices of alcohol consumption. Methods: Hospital Episode Statistics for admissions were obtained from the Department of Health and mortality data from the Office for National Statistics. Alcohol consumption data were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
5
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 20 publications
(49 reference statements)
4
64
5
3
Order By: Relevance
“…The incidence in Europe and United states ranges from 20 to over 70 per 100,000 population. 2,3 Computed tomography gives a global picture of the pathology and complications of acute pancreatitis. CT has the advantages over other imaging techniques that it is accurate in establishing the diagnosis, and in assessing for complications.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence in Europe and United states ranges from 20 to over 70 per 100,000 population. 2,3 Computed tomography gives a global picture of the pathology and complications of acute pancreatitis. CT has the advantages over other imaging techniques that it is accurate in establishing the diagnosis, and in assessing for complications.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last four decades, the overall incidence of acute pancreatitis seems to be increasing, not only in the United States, but also in different European countries: England,Scotland,Denmark,Sweden, Finland,Germany and the Netherlands [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands the incidence of acute pancreatitis increased by 28% between 1985 and 1995 .In the United Kingdom the incidence of acute pancreatitis rised by a factor of ten from 1960 to the 80s [5]. Population studies from Europe and the United States have described the epidemiology of first attacks of acute pancreatitis, mostly in a retrospective way; only few report etiology-specific incidence trends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 35-year period of the study, the mortality rate for acute pancreatitis remained relatively stable at approximately 5% (3). Another study from England also reported an increase in the incidence of acute and chronic pancreatitis from 14.5 per 100 000 to 20.7 POLSKI PRZEGLĄD CHIRURGICZNY 10.2478/v10035-007-0036-4 2007, 79,3,[239][240][241][242][243][244][245][246][247][248][249][250][251][252][253][254][255] per 100 000 over the 10-year period between 1990 and 2000 (7).…”
mentioning
confidence: 99%